Following the precepts of the teacher - V. M. Malov; E. B. Eroshevskaya; I. V. Malov (Российский офтальмологический журнал, 2022)
A short biography of an outstanding Russian ophthalmologist, Professor Tikhon Ivanovich Eroshevsky is presented to commemorate his 120th anniversary. Professor Eroshevsky made a significant contribution to ophthalmological science and practice. He was the founder of a well-known scientific school.